2008
DOI: 10.1111/j.1745-459x.2008.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Palate Cleansers for Evaluating Sourness

Abstract: The objective of this study was to compare four palate cleansing strategies (crackers, carrots, water and nothing) for their effectiveness in evaluating the sourness of a fruit-flavored beverage. Forty panelists rated the sourness intensity of five orange drink samples that varied in citric acid content. Each subject participated in four sessions, one for each palate cleanser. As expected, sourness increased with increasing citric acid content. There were no significant differences between any of the palate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Though bitterness is known to linger and build with repeated exposures (Lea & Arnold, 1978;Brannan et al, 2001;Johnson & Vickers, 2004), we had not observed a similar trend with sourness ratings in previous studies of a similar nature (Lee & Vickers, 2008;Vickers et al, 2008). However, in both of those studies, we used citric and phosphoric acids, which are both weak acids.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Though bitterness is known to linger and build with repeated exposures (Lea & Arnold, 1978;Brannan et al, 2001;Johnson & Vickers, 2004), we had not observed a similar trend with sourness ratings in previous studies of a similar nature (Lee & Vickers, 2008;Vickers et al, 2008). However, in both of those studies, we used citric and phosphoric acids, which are both weak acids.…”
Section: Discussioncontrasting
confidence: 77%
“…Buffering capacity could have been increased by the proteins in skim milk, the carboxyl groups of CMC or by the increased quantity of saliva from chewing wax. Other cleansers, like crackers, may have raised the oral pH between samples (Vickers, Morris, & Savaria, 2008) and limited the subsequent pH drop from the following acid solution. Using water as a cleanser, however, likely diluted the saliva that was present and diminished its buffering capacity.…”
Section: Discussionmentioning
confidence: 98%
“…The 100 mL amounts, in their plastic cups, were placed in the test room one hour prior to the experiment and the room temperature was kept constant at 22 • C to ensure maximum taste sensitivity in the 20 to 30 • C temperature range [65,66]. Palate cleansing was performed to remove any residue before and between taste samples to minimise carryover effects [67][68][69]. Water, one of the most effective palate cleansers for sweetness [70], was used in this study.…”
Section: Taste Stimuli and Palate Cleansermentioning
confidence: 99%
“…One issue in accurately evaluating multiple products in one session, is the need for panelists to cleanse their palate. Many items have been suggested to work as palate cleansers and many products generally have been discounted when formally tested (see, e.g., Lee & Vickers, 2010;Naswari & Pangborn, 1990;Vickers et al, 2008). However, in some studies options such as crackers (Ross et al, 2007) or mozzarella cheese, cucumbers, apples, and unsalted crackers (Lucak & Delwiche, 2009) worked as a palate cleanser.…”
Section: Acridmentioning
confidence: 99%